Governance Efficiency in Conditions of the World Economy Globalization and Digitalization - USHAKOV, Denis S.; SIGIDOV, Yuriy I.; GRIBINCEA, Alexandru; BIRCA, Iulita; MASHAL, Lama (Journal of Advanced Research in Law and Economics, 2019)
The growth of internationalization, globalization have transformed the interaction within the ‘government-business’ framework, providing additional capacity to both its members and depriving them of such. The concept of ‘state's capacity’ in many contexts it is now used quite widely. This paper aims to analyze the modern transformations of principles of foreign economic activities regulation; determined by transnationalization and by the global trend of innovative modernization; to identify the main characteristics, inherent to present stage of world economic development requirements; to analyze the effectiveness of informatization and net-working, as guidelines for world economy controlling. As the most significant scientific results of the research are the following results: in the globalization context the government capacity to regulate the economy and the businesses ability for self-regulation have been greatly undermined; for avoiding the extreme measures, the modern governments need today to review the general principles of foreign economic control, and to create a modern, conforming to the scientific and technical progress, infrastructure for implementing their regulatory competencies; sustainable economic progress in a complex system of world economic relations requires from the modern government to develop a set of measures, aimed at consolidating the domestic business, etc. The results, obtained by the study, can be used in the process of developing the concepts, strategies and public policy in the sphere of governmental functions digitalization and problem of information inequality elimination, in the face of increasing international integration of e-business forms.